The role of Perceptions of Context (PoC) on Job Burnout in health services organizations - De Simone, Silvia; Cicotto, Gianfranco; Borgogni, Laura (La Medicina del Lavoro, 2018)
Background: Several empirical studies have investigated Job Burnout and its predictors, underlining the role of situational and organizational factors. The Perceptions of Context construct (PoC) has yet to be studied in healthcare contexts. Objectives: The aim of the study is to broaden the knowledge of the Job Burnout determinants focusing on the dimensions of the context and to integrate research in this field with a construct that emphasizes the relational dimension, the Interpersonal Strain. Methods: 105 health-care workers of an Italian organization have completed a self-report questionnaire including the following scales: Perceptions of Context - Perceptions of the social component (colleagues, teamwork, supervisor, management, collaboration of patients and family members, collaboration between wards) and Perceptions of the task (workload and time pressure); MBI-GS (Exhaustion and Cynicism); ISW Scale (Interpersonal Strain). Results: The results confirm the association between the PoC and Job Burnout and show the cross-sectional role played by Perception of Time Pressure on all three dimensions of Job Burnout. An interesting result is the role played by the perceptions of the social component, in particular the role of Supervisor Perceptions in predicting Exhaustion and Cynicism, and the role of Teamwork Perceptions in predicting Interpersonal Strain. Significant differences between the PoCs and the membership ward emerged. Conclusions: Based on our results, it is possible to plan focused prevention and intervention actions.